2021
DOI: 10.1371/journal.pone.0250938
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic and stability of stock market—A sectoral approach

Abstract: The COVID-19 pandemic seems to be the most important phenomenon observed from March 2020 in virtually all countries of the world. The necessity to prevent the spread of COVID-19 and keep health care systems efficient resulted in the forced, drastic limitation of economic activity. Many service sectors were hit particularly hard with this but industry and agriculture were also affected. In particular, the pandemic substantially influenced financial markets and we can observe that some markets or instruments var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 89 publications
0
27
0
2
Order By: Relevance
“…) of the squared eigenvector components v Some deeper insight into the cross-correlation structure of the cryptocurrency market can be gained by transforming the q-dependent detrened correlation matrix C q (s) into a related distance matrix D q (s), whose elements are defined by Equation (7). The latter is used as a basis for creating a minimum spanning tree, in which each node represents a particular cryptocurrency and each weighted edge represent the metric distance between a pair of assets or, equivalently, the detrended cross-correlation coefficient.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…) of the squared eigenvector components v Some deeper insight into the cross-correlation structure of the cryptocurrency market can be gained by transforming the q-dependent detrened correlation matrix C q (s) into a related distance matrix D q (s), whose elements are defined by Equation (7). The latter is used as a basis for creating a minimum spanning tree, in which each node represents a particular cryptocurrency and each weighted edge represent the metric distance between a pair of assets or, equivalently, the detrended cross-correlation coefficient.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past few years, two processes have had a particularly strong impact on financial markets: the emergence of the cryptocurrency market [ 1 , 2 , 3 , 4 , 5 ] and the COVID-19 pandemic [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Each of these processes alone has already been a topic in numerous pieces of the scientific literature, but they also were studied together [ 5 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is difficult to compare the results of our study with those obtained by other authors and additionally related to the impact of COVID-19 on the energy and fuel sector. Buszko et al [76] in their research address the problem of stock market stability during the first wave of the COVID-19 pandemic. They analyse the Warsaw Stock Exchange.…”
Section: Discussionmentioning
confidence: 99%
“…To further elucidate the equity market response to the COVID-19 issue, some empirical studies have focused on the market performance through its constituents, on a sector level [37][38]40]. For example, He et al [38] reported the manufacturing, information technology, education and health-care industries in China as being the most resilient sectors within the pandemic timeline; while the transportation, mining, electricity and environment industries are found to be the most vulnerable to the COVID-19 crisis, in the Chinese market.…”
Section: Introductionmentioning
confidence: 99%
“…Alam et al [40] inspected the sectoral performance of the Australian equity market in the immediate days following COVID-19 announcement and found a good performance for the telecommunications, pharmaceuticals and healthcare sectors, in this period. Buszko et al [37] analyzed the sector constituents of the Warsaw Stock Exchange during COVID-19 pandemic and found the construction, information technology, game developers, biotechnology, telecoms and new technology sectors to exhibit positive relative change in their average prices, in the medium-term period after the crisis began. While some other sectorsautomobiles, banking, chemical, clothes, energy, food, mining, oil & gas, pharmaceutical and real estate-were found unprofitable within the same timeline, in that market.…”
Section: Introductionmentioning
confidence: 99%